A REVIEW OF BOTANY, THERAPEUTIC VALUE, PHYTOCHEMISTRY, AND PHARMACOLOGY OF CUSSONIA PANICULATA: ETHNOPHARMACOLOGY OF CUSSONIA PANICULATA - ALFRED MAROYI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Cussonia paniculata is a small tree widely used as herbal medicine throughout its distributional range in southern Africa. This study is aimed at providing a critical review of the botany, biological activities, phytochemistry, and medicinal uses of C. paniculata. Documented information on the botany, biological activities, medicinal uses, and phytochemistry of C. paniculata was collected from several online sources which included BMC, Scopus, SciFinder, Google Scholar, Science Direct, Elsevier, PubMed, and Web of Science. Additional information on the botany, biological activities, phytochemistry, and medicinal uses of C. paniculata was gathered from pre-electronic sources such as book chapters, books, journal articles, and scientific publications sourced from the University library. This study showed that the bark, fruits, leaves, roots, and stems of C. paniculata are used as emetic, immune booster, and herbal medicine for dysmenorrhea, intestinal parasites and worms, mental problems, boils, shingles and skin diseases, indigestion and stomach complaints, sores, and wounds. Phytochemical compounds identified from the leaves of C. paniculata include acetylated triterpene glycosides, unacetylated triterpene glycosides, flavonoid, steroidal saponin, and triterpenoid saponins. Pharmacological research revealed that C. paniculata extracts have analgesic, antibacterial, anticancer, anti-inflammatory, antiplasmodial, antiprotozoan, Aβ42 protein reduction, and cytotoxicity activities. Future research should focus on evaluating the phytochemical, pharmacological, and toxicological properties of C. paniculata crude extracts as well as compounds isolated from the species.